Educational and social priorities of improving the system of physical education students - Vasylyuk V.N (Kharkov National Pedagogical University, 2013)
Purpose - pedagogical and sociological research priorities in the system of physical education of students. The study involved more than 800 students. Described educational and social priorities of improving the system of physical education students, the basic ideas and principles of conservation and health by means of physical culture. The necessity of the restructuring and improvement of the physical education of youth in accordance with the level of social demands. It was found that the problem of physical culture as a social phenomenon is closely linked to the problem of formation of physical culture of the individual. In turn, the problem of identity formation in physical education is a challenge to improve the foundations of physical education among young people and students. Confirmed the hypothesis on the need for adjustment and improvement of the physical education of youth.